Egg Quality Characteristics, Phenotypic Correlations and Prediction of Egg Weight in Three (Naked Neck, Frizzled Feather and Normal Feathered) Nigerian Local Chickens - Udoh , U.H.; Okon, B.; Udoh, A.P. (International Journal of Poultry Science, 2012)
A study was conducted to determine egg quality characteristics, phenotypic correlations and prediction of egg weight from egg quality parameters in three varieties (naked neck, frizzled feather and normal feathered) of local chickens in Akwa Ibom State, Southeastern Nigeria. A total of 600 eggs (200 each of naked neck, frizzled feather and normal feathered varieties) were collected. External and internal defects were computed and expressed as percentage of total egg production and summed up to obtain the total defects score for each variety. Egg quality parameters were compared between varieties using Multivariate General Linear Model of SPSS version 17.0 for ANOVA. Means were tested using Duncan’s Multiple Range Test. Phenotypic correlations of egg quality parameters and prediction of egg weight using yolk weight, yolk width and albumen weight was done. Lowest total defects score (11.00%) was recorded for frizzled feather, 11.63% for naked neck and the highest (12.65%) for normal feathered. Egg weight differed significantly (p0.05). Mean highest value of 82.49% for haugh unit by naked neck was significantly different (p